The impact of social isolation on the COVID-19 pandemic on access to HIV treatment and prevention services (Research, Society and Development, 2021)
The World Health Organization, in March 2020, declared COVID-19 as a pandemic, recommending measures for the prevention, control and treatment of the disease. One of the main measures, social isolation, resulted in the suspension of several procedures in health services. The reorganization of services aimed at the outpatient care of pathologies caused incalculable losses and consequences in the continuity of treatment. The study aims to discuss the consequences of social distance measures and the organization of outpatient services aimed at caring for people living with HIV during the COVID-19 pandemic. Method: an integrative review, carried out on the CAPES Journals Portal, using studies available in full, indexed on the PUBMED portal, containing the descriptors: HIV, Antiretroviral Therapy, Social Isolation. The sample resulted from 9 studies selected after the inclusion and exclusion criteria. Results: The pandemic directly interfered in the treatment and provision of services for people living with HIV. There was a decrease in the routine of testing, rescheduling or suppression of the hours of routine appointments and a decrease in the distribution of medications. Conclusion: Despite the risk situation, care in health services for key populations must be guaranteed, qualitatively and quantitatively, and it is the managers' responsibility to reorganize the services, seeking to eradicate interruptions in care and improve the care provided.